On the Extensional Rheology of Polymer Melts and Concentrated Solutions - Sridhar, T; Acharya, Mohini; Nguyen, D. A; Bhattacharjee, P. K (Macromolecules, 2014)
We examine the influence of the number of entanglements per chain (Z) on the uniaxial extensional rheology of polymer melts and concentrated solutions. We subject fluids with wide range of Z (13–51) to uniaxial extensional flow at strain rates that also spans a wide range: starting at strain rates that much less than the inverse of the longest measurable relaxation time of the chains to strain rates that are in excess of the order of the inverse of the Rouse time of the chain. The results show that the value of Z critically influences extensional flow at all strain rates examined. The combination of results presented here and those from recent literature clearly establish areas where the agreement between tube theory and experiments is less than satisfactory. These differences are particularly evident at strain rates wherein chain stretching is expected to play a role. There are also differences in the behavior of polystyrene melts and other systems investigated. Taking together exiting data indicate that the universality of the tube model may break down at large strain rates. It is possible that the monomeric friction coefficient depends sensitively on molecular architecture and the surrounding environment. The presence of pendant groups on the monomer background may influence the friction coefficient. Predicting this apriori remains a challenge. Additionally we show that the parameter λmax/Z, where λmax is the ratio of the maximum length of a polymer chain to its equilibrium length, influences the flow behavior to the extent that fluids having equal values of λmax/Z demonstrate similar rheological behavior at all deformation rates when the extensional flow response is suitably scaled. We also compare our results with those obtained on other polymer melts in uniaxial extensional flow reported previously in literature.